Additive Manufacturing of Watertight ABS Parts and Its Use for Chemical Metal Plating - Philipp Zimmermann; Christoph Schammel; Jürgen Nagel (Macromolecular Materials and Engineering)
Abstract One of the most frequently used polymers in the galvanic industry as well as for Fused Filament Fabrication (FFF) is the terpolymer of acrylonitrile butadiene styrene (ABS). Its surface is etched in chromosulfuric acid to enable the chemical deposition of a metal. The use of chromium (Cr)(VI) compounds is restricted in the European Union (EU) since 2017. A new plating process is proposed here that does not rely on etching. Instead, double bonds on the ABS surface are converted to epoxides, followed by grafting of a polyethylenimine (PEI) to the surface. The so modified plastic is an ideal starting point for metal plating. Printing often leads to the formation of voids between strands and layers, which hinders subsequent wet processing. The plating process introduced here requires high demands on the water tightness of parts. The proposed printing procedure reduces the degree of penetration of water from 50% to less than 0.1% at 2 bar water pressure. The combination of the new printing procedure with the new plating process results in the deposition of industrial relevant nickel (Ni) layers. The cross‐hatch test followed by a peel test exhibits values of zero, pointing to the high adhesion of Ni to ABS.